2019
DOI: 10.29244/medkon.24.3.245-251
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Tree Species in Muaro Jambi Temple Complex

Abstract: Kompleks Candi Muaro Jambi merupakan salah satu wisata andalan Provinsi Jambi yang mulai dikenal di dalam maupun di luar negeri. Keberadaan jenis-jenis pohon hutan yang terdapat di kompleks percandian Muaro Jambi sangat penting untuk dipertahankan. Kegiatan eksplorasi botani di kompleks percandian Muaro Jambi sangat penting untuk dilaksanakan dalam rangka melakukan inventarisasi dan identifikasi jenis-jenis pohon yang ada. Data yang diperoleh akan berguna dalam kegiatan konservasi dan pelestarian tumbuhan huta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The most abundant species was Yellow-vented Bulbul (Pycnonotus goiavier) with a total of 66 records followed by Ashy Tailorbird (Orthotomus ruficeps) with a total of 50 records. Ashy Tailorbird is a member of the family Sylviidae whose major diet is insect and is classifiedas primary andsecondary insectivores [6], therefore is highlypotential in controlling the insect pest.…”
Section: Abundance Dominance and Diversity Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most abundant species was Yellow-vented Bulbul (Pycnonotus goiavier) with a total of 66 records followed by Ashy Tailorbird (Orthotomus ruficeps) with a total of 50 records. Ashy Tailorbird is a member of the family Sylviidae whose major diet is insect and is classifiedas primary andsecondary insectivores [6], therefore is highlypotential in controlling the insect pest.…”
Section: Abundance Dominance and Diversity Indicesmentioning
confidence: 99%
“…Information on the diet of birds is necessaryto support pest control in agroecosystem. A study on the diet of insectivorous birds in agricultural areasshowed that most birds tend to feed on insect pests from the order of Coleoptera, Lepidoptera and Orthoptera [6]. This finding showed that birds are potential to be used as pest control in oil palm plantation whose major insect pest are from the order Lepidoptera.…”
Section: Introductionmentioning
confidence: 99%
“…Ukuran bungan kecil tersusun dengan malai, bunga berkelamin tunggal atau bunga banci, agak zigomorf atau aktinomorf, mempunyai kelopak biasanya berjumlah 5, benang sari mempunyai jumlah yang sama atau dua kali lipat dengan mahkota. Buahnya termasuk tipe buah batu dan buni (Tamin et al, 2019).…”
Section: Pendahuluanunclassified
“…Jambi Province is rich in biological and cultural variety (Pamungkas and Agustiningsih 2018;Tamin et al 2019). The total forest area in Jambi Province is 2,098,535 ha (Dinas Kehutanan Jambi 2019).…”
Section: Introductionmentioning
confidence: 99%